Edukasi Keamanan AWS: Mengamankan Akun, Data, dan Kepatuhan Cloud dengan AWS IAM - Hamdani, Ibnu Mansyur; Syahadi, Adi; Julyaningsih, A. Hermina; Arminas, Arminas (Universitas Methodist Indonesia, 2025)
Cloud computing service security is a crucial aspect in managing data and information technology infrastructure. Amazon Web Services (AWS) provides security features such as AWS Identity and Access Management (IAM) to control access to resources. However, the lack of user understanding in implementing this system increases the risk of data leaks and cyber attacks. This community service activity aims to improve digital security literacy, especially in the use of AWS IAM. The training was held online on February 2, 2025 via Zoom and was attended by 24 participants from a total of 30 registrants. The methods used include theory and direct practice using an AWS Academy account. Evaluation was carried out through pre-tests and post-tests as well as a Google Form survey. The results showed an increase in understanding with an average pre-test score of 60 increasing to 85 in the post-test. In addition, 92% of participants stated that the material presented was relevant, 88% felt the training was practically useful, and 90% were more confident in managing their AWS accounts. These results show that education about AWS security is essential to reduce the risk of misconfiguration and improve the security of cloud-based systems.